Contribuições para o estabelecimento de padrões para águas de reúso através da análise de risco - Scortegagna, Vinícius (2011)
In Brazil still prevails a culture of waste in relation to water, this is mainly due to the misconception that the water reserves are infinite. The search for ways to curb water demand, through programs of rational use, programs to make users aware of the value of the water and by the implementation of charging for the use of this substance, beyond the increasing of the supply through the adoption of water reuse systems, are the solutions that became researchers center of attention. Considering the expansion of the practice of reusing, questions of public health appear, since ensuring the safety of users of this substance is an aspect of fundamental importance. The research motivation is to collaborate to setting standards for safe reuse of gray water , from the application of methodologies of risk analysis, assisting decision makers in judgments in regard to acceptable levels of pollutants existents on reuse water, according to the proposed use. To perform the analysis was used the Preliminary Hazard Analysis (PHA) and the analytic hierarchy process. Methods were applied by creating a risk scenario to the reuse practice. Parameters to be raised were identified, in order to contemplate the analysis of risk, they are: Total coliforms, Fecal coliforms, Escherichia coli, Suspended Solids and Turbidity. Microbiological parameters were listed because they are the main causative agents of waterborne diseases; physical parameters were also listed in function of the visual aspect of reuse water, because they are inducers of disapproval from the part of users. For the PHA the risk scale goes from one to five, number one intend negligible and five intend critical. Were covered 42 cases of exposure of the user to the listed contaminants, as a result of PHA, nineteen were considered at risk five (critical), one risk four (seriously), nine risk three (moderate) and thirteen risk one (negligible). The application of analytic hierarchy process showed as the best option to reuse gray water on installations of fire combat fire and on garden watering, since they contemplate the lower risk of contamination or injury to the user, and used the largest volume, becoming a water economy. As the most promising source of gray water the effluent from the service areas were the effluents that showed the best results on the analysis, based on the volume generated and the quality of the effluent